Introduction and Testing of an Alternative Control Approach for a Robotic Prosthetic Arm - Griggs, Lauren; Fahimi, Farbod (The open biomedical engineering journal, 2014)
Commercially available robotic prosthetic arms currently use independent joint control. An alternative controller involving only control of the hand in a Cartesian frame rather than controlling each joint independently is proposed and tested. An experimental 4DOF robotic arm was used as the platform for testing the proposed control approach. As opposed to joint control, Cartesian control requires the solution to the inverse kinematics problem. The inverse kinematics solution was developed for the robotic arm using the extended Jacobian method. The two control methodologies, joint control and Cartesian control, were tested on five able-bodied human subjects. Improvement of one control methodology over the other was measured by the time it took for the subjects to complete a simple motor task. The timed trial results indicated that Cartesian control was both more intuitive and more effective than joint control. So, the results suggest that much improvement can be achieved by using the proposed Cartesian control methodology.